New care pathways for supporting transitional care from hospitals to home using AI and personalized digital assistance - Ionut Anghel; Tudor Cioara; Roberta Bevilacqua; Federico Barbarossa; Terje Grimstad; Riitta Hellman; Arnor Solberg; Lars Thomas Boye; Ovidiu Anchidin; Ancuta Nemes; Camilla Gabrielsen (Scientific Reports)
Abstract Transitional care may play a vital role in the sustainability of Europe’s future healthcare system, offering solutions for relocating patient care from hospital to home, therefore addressing the growing demand for medical care as the population is ageing. Re-hospitalization for the same initial pathological cause is a recurrent problem among older adults with chronic conditions such as heart failure or chronic obstructive pulmonary disease. However, to be effective, it is nowadays essential to integrate into the transitional care process innovative Information and Communications Technology technologies to ensure that patients with comorbidities experience a smooth and coordinated transition from hospitals or care centers to home, thereby reducing the risk of rehospitalization. In this paper, we present an overview of the integration of Internet of Things, artificial intelligence, and digital assistance technologies with traditional care pathways to address the challenges and needs of healthcare systems in Europe. We identify the current gaps in transitional care and define the technology mapping to enhance the care pathways, aiming to improve patient outcomes, safety, and quality of life, avoiding hospital readmissions. Finally, we define the trial setup and evaluation methodology needed to provide clinical evidence that supports the positive impact of technology integration on patient care and discuss the potential effects on the healthcare system.